KEEFEKTIFAN PEMBELAJARAN MEMBACA DENGAN MENGGUNAKAN PENGUATAN DAN MEDIA GAMBAR - Suyatinah Suyatinah (Universitas Negeri Yogyakarta, 2006)
Abstract The purpose of the research is to improve: (a) the student reading skill at the first grade of elementary school, (b) the learning reading motivation, (c) the learning reading attention, and (d) the activity of the learning reading at the first grade of elementary school. This study is a classroom action research and the subjects are the teacher and the students of the first grade of Sapen, Yogyakarta Elementary School. The research consists of three cycles. The study involved, the teacher of the improving of the effectiveness of the teaching learning reading in the first grade of state Elementary School. The results of this research are as follows:a) the students reading skill, b) the learning reading motivation c) the attention; The Elementary School students activity in Sapen, Yogyakarta gets improvement after giving the implementation of the action; the teacher is able to construct the design of action research on reading learning teaching by using the reinforcement and drawing media; the teacher and the students respond the implementation of the teaching learning reading using reinforcement role and drawing media positively. Keywords: reading skill, reinforcement, and drawing media